In vitro fertilization causes excessive glycogen accumulation in mouse placenta. (October 2021) - Dong, Jie; Guo, Xiangyu; Qian, Chenxi; Wang, Jingjing; Lei, Hui; Chen, Shuqiang; Wang, Xiaohong
Abstract: Introduction: Children conceived by assisted reproductive technologies have a high risk of suffering from obstetrical complications and long-term health problems, but the related mechanisms are not fully understood. Normal placental function is closely linked with foetal growth and future health. Given the significance of glycogen metabolism in placentas, we investigated the effect of in vitro fertilization (IVF) on glycogen storage in placentas using a mouse model. Methods: Mouse placentas were collected at E18.5 after natural mating or IVF, and the placental and foetal weights were recorded. The quantitative assay kit and histological staining were used to measure the glycogen content. Additionally, we detected the expression of multiple genes associated with glycogen synthesis/decomposition, glucose transporters, and the phosphorylation of Akt and Gsk3β. Results: Our findings showed that IVF resulted in a significantly increased mouse placental weight and enlarged junctional area. We found, compared to the control, excessive glycogen was accumulated in IVF placentas. However, we observed that multiple genes involved in glycogen generation ( Gsk3b, Phka1, Phkb, Phkg1, and Phkg2 ) and glycogenolysis ( Agl and Pygm ) had lower mRNA levels in IVF placentas. Moreover, the expression levels of glycogen synthase, phosphorylase, Glut1, and Glut3 were significantly decreased in IVF placentas. The phosphorylation activities of Akt Ser473 and Gsk3β Ser9 were inhibited in IVF placentas. Discussion: IVF leads to enlarged mouse placentas with excessive glycogen storage in late pregnancy, and these abnormal changes may be associated with the activation of the Akt-Gsk3β pathway. Highlights: IVF leads to enlarged placental weight but low placental efficiency in mice. The excessive glycogen accumulation occurs in IVF mouse placenta. The activated Akt-Gsk3β may be linked with high glycogen storage in IVF placenta. Glycogen storage increase in placenta may be a result of adaptive response to IVF.